'Fertility' and the Carnival 1: Symbolic Effectiveness, Emic Beliefs, and the Re-enchantment of Europe. Issue 1 (2nd January 2017) - Testa, Alessandro
Abstract: This article examines European festive culture through the lens of two ethnographic case studies of carnivals, conducted in Italy and the Czech Republic, respectively. The article considers the general problem of studying festivals in Europe today, and then focuses on the emic beliefs related to the 'ritual magical' acts of these two carnivals, their social relevance, their effectiveness, and the meanings and functions to which they are bound today. I argue that these acts constitute empirical evidence that supports theories about the 're-enchantment' of Europe in post-modern times. This article is the first part of a broader study divided into two parts.